1999
DOI: 10.1016/s0092-8674(00)80659-5
|View full text |Cite
|
Sign up to set email alerts
|

Transducing the Dpp Morphogen Gradient in the Wing of Drosophila

Abstract: Dpp, a TGFbeta, organizes pattern in the Drosophila wing by acting as a graded morphogen, activating different targets above distinct threshold concentrations. Like other TGFbetas, Dpp appears to induce transcription directly via activation of a SMAD, Mad. However, here we demonstrate that Dpp can also control gene expression indirectly by downregulating the expression of the brinker gene, which encodes a putative transcription factor that functions to repress Dpp targets. The medial-to-lateral Dpp gradient al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
291
1
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 271 publications
(310 citation statements)
references
References 44 publications
16
291
1
2
Order By: Relevance
“…3A, top). The gene brinker encodes a repressor of direct BMP target genes transcription (Campbell and Tomlinson, 1999;Jaźwiń ska et al, 1999a,b;Minami et al, 1999) and its widespread expression is controlled by yet to be characterized transcriptional activators (Yao et al, 2008). DPP/BMP signaling alleviates Brinker-mediated repression by inhibiting brinker transcription ( Fig.…”
Section: Schnurri a Transcriptional Partner With Multiple Personalitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…3A, top). The gene brinker encodes a repressor of direct BMP target genes transcription (Campbell and Tomlinson, 1999;Jaźwiń ska et al, 1999a,b;Minami et al, 1999) and its widespread expression is controlled by yet to be characterized transcriptional activators (Yao et al, 2008). DPP/BMP signaling alleviates Brinker-mediated repression by inhibiting brinker transcription ( Fig.…”
Section: Schnurri a Transcriptional Partner With Multiple Personalitiesmentioning
confidence: 99%
“…DPP/BMP signaling alleviates Brinker-mediated repression by inhibiting brinker transcription ( Fig. 3A, bottom ;Campbell and Tomlinson, 1999;Jaźwiń ska et al, 1999a,b;Minami et al, 1999). A critical transcription factor mediating this DPP-dependent repression of brinker is the zinc finger DNA-binding protein Schnurri (Shn; German for whiskers; Arora et al, 1995;Grieder et al, 1995;Staehling-Hampton et al, 1995).…”
Section: Schnurri a Transcriptional Partner With Multiple Personalitiesmentioning
confidence: 99%
“…A potential candidate, the transcriptional repressor of Dpp target genes, Brk (Campbell and Tomlinson, 1999;Jazwinska et al, 1999;Kirkpatrick et al, 2001;Minami et al, 1999;Rushlow et al, 2001;Saller and Bienz, 2001;Sivasankaran et al, 2000;Zhang et al, 2001), is suggested by evidence indicating that Dpp is required to override REPE function. In the wing and leg imaginal discs, brk expression is repressed by and is roughly reciprocal to Dpp signaling.…”
Section: Brinker Opposes Hh Signaling Through the D-h Enhancermentioning
confidence: 99%
“…However, more recent studies indicate that Dpp also regulates its target genes by blocking expression of a repressor. In imaginal discs, Mad/Med and the zinc-finger protein Shn, repress expression of the brinker (brk) gene (Marty et al, 2000;Muller et al, 2003;Torres-Vazquez et al, 2000), which encodes a direct repressor of Dpp target genes (Campbell and Tomlinson, 1999;Jazwinska et al, 1999;Kirkpatrick et al, 2001;Minami et al, 1999;Rushlow et al, 2001;Saller and Bienz, 2001;Sivasankaran et al, 2000;Zhang et al, 2001). The Brk repressor is distributed in a gradient reciprocal to Dpp signaling and functions to delimit the domains of Dpp target gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…brk encodes a transcriptional repressor and is a key target of the Dpp pathway that is negatively regulated by Dpp signaling throughout embryonic and larval development [56,57]. brk is highly expressed in the lateral regions of the wing disc, forming a gradient reciprocal to the Dpp gradient (Figure 1M).…”
Section: Resultsmentioning
confidence: 99%